Crisis and corporate social responsibility: Threat or opportunity? - Belén Fernández-Feijóo Souto (International Journal of Economic Sciences and Applied Research, 2009)
The objective of this paper is to reflect on the consequences of the current economic and financial crisis on Corporate Social Responsibility (CSR), a concept of great importance nowadays. The core approach is the possible link between CSR and the crisis, if both elements can be combined. After an introduction to the current economic and financial situation, some conceptualizations about CSR are made to clarify the perspective used for this complex and incompletely defined concept. The last part of the paper presents an approach to the combination of both concepts, concluding with the idea that CSR in crisis periods can be converted from being a threat to an opportunity.
Keywords: M10; M14; M21; 330; crisis; corporate social responsibility; business ethics